Whole blood versus red cell concentrates for children with severe anaemia: a secondary analysis of the Transfusion and Treatment of African Children (TRACT) trial - George, EC; Uyoga, S; M'baya, B; Kyeyune Byabazair, D; Kiguli, S; Olupot-Olupot, P; Opoka, R; Chagaluka, G; Alaroker, F; Williams, TN; Bates, I; Mbanya, D; et al. (Elsevier, 2022)
Background: The TRACT trial established the timing of transfusion in children with uncomplicated anaemia (haemoglobin 4–6 g/dL) and the optimal volume (20 vs 30 mL/kg whole blood or 10 vs 15 mL/kg red cell concentrates) for transfusion in children admitted to hospital with severe anaemia (haemoglobin <6 g/dL) on day 28 mortality (primary endpoint). Because data on the safety of blood components are scarce, we conducted a secondary analysis to examine the safety and efficacy of different pack types (whole blood vs red cell concentrates) on clinical outcomes.